PEMETAAN ‘KEBAYA INDONESIA’ BERDASAR RAGAM BUSANA ATASAN PAKAIAN DAERAH DI INDONESIA - Ardhiati, Yuke; Muchlison, Sonny; Pramestuti, Agustina Wilujeng; Nafasia, Sahadat (Universitas Mercu Buana, 2023)
Kebaya has been recognized as the Indonesian national costume in Jawa, Bali, Lombok and Riau. Kebaya identified by kutuburu as fleas or bef, it roles as a 'bridge' for the pairs of folding collars, and also the kebaya silhouette itself. Even though it sustains since Colonials era and well known in aboard, unfortunately kebaya was not mentioned either in the Presidential Decree in 1972 and 1990, the Law of the Republic of Indonesia No. 9 of 2010 related to the dress code the State Events till the Presidential Regulation in 2018. All presidential regulations focussed on men when they will attend state events. Because it is not specifically stated, the position of the kebaya is interpreted as the equivalent of other regional clothing superiors. This is not realized by the community, so it is necessary to unite aspirations in order to be easier to submit to Kebaya Goes to UNESCO as a single nomination. This is a grounded research-based in qualitative research aims to mapping all various regional tops, into one terminology that can represent one meaning as Indonesian Kebaya. The research results in the form of mapping of the ‘Indonesian Kebaya' are expected to obtain a legality as THE KEBAYA INDONESIA, so that it is meaningful to support the Kebaya Indonesia Goes To UNESCO.